2020
DOI: 10.14202/vetworld.2020.2046-2052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the bovine TG5 gene polymorphism on milk- and meat-producing ability

Abstract: Aim: This study aimed to determine the effect of thyroglobulin (TG5) gene polymorphism on milk and meat productivity in the various cattle breeds currently bred in the Republic of Bashkortostan. Materials and Methods: The test was performed on dairy cattle of Black-and-White, Bestuzhev, and Simmental breeds, and meat cattle of Hereford and limousine breeds. The purpose of the test was to search for associations between the polymorphic alleles of the thyroglobulin (TG5) gene and economically useful traits. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several studies have reported the association of MASP2, TG5, and DQA1genes polymorphism with production and components in cattle (Al-Waith et al, 2018;Zhang et al, 2019;Dolmatova et al, 2020). However, unlike our study, all of these studies investigated the association of gene polymorphism in only one breed of cattle.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Several studies have reported the association of MASP2, TG5, and DQA1genes polymorphism with production and components in cattle (Al-Waith et al, 2018;Zhang et al, 2019;Dolmatova et al, 2020). However, unlike our study, all of these studies investigated the association of gene polymorphism in only one breed of cattle.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, thyroid hormones influence lipid metabolism and adipocyte development into adipose tissue. Consequently, the thyroglobulin gene is a functional and positional candidate gene that influences fat accumulation in tissues, including milk (Dolmatova et al, 2020). A single-nucleotide polymorphism in the 5′ untranslated region of the TG5 gene is used for marker-based selection targeted at raising marbling (Carvalho et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hormone release occurs due to the stimulation of the thyroid cells by the thyrotropic hormone (TSH). Further activity by the released hormones stimulates the hepatic processes of gluconeogenesis and lipogenesis, as well as the occurrence of glycogenolysis [ 62 ].…”
Section: Thyroglobulinmentioning
confidence: 99%
“…Nevertheless, the fat content and FA composition of beef remain important characteristics for both producers and consumers [ 9 ]. Many researchers have identified polymorphisms in the leptin ( LEP ) and thyroglobulin ( TG5 ) genes as significant genetic factors that influence the intensity and characteristics of fat metabolism in the body [ 10 , 11 ]. Thus, the C422T polymorphism occurs in the 5’-promoter region of the TG5 gene [ 12 ].…”
Section: Introductionmentioning
confidence: 99%